Plagiarism and Artificial Intelligence: Balancing Innovation with Academic Integrity - Aryal, Marisha; Sharma, Apurb (Nepalese Heart Journal, 2025)
Currently, the intersection of artificial intelligence (AI) and plagiarism has become a pressing issue in academia, journalism, and creative fields. This convergence raises important questions about authorship, originality, and the ethical considerations surrounding the use of technology for content generation. The rapid evolution of AI tools invites profound reflection on how these technologies can affect integrity and creativity in the production of academic and creative works. Some individuals argue that using AI is advantageous, particularly for non-native speakers, while others contend that it may lead to scientific misconduct. Therefore, striking the right balance between innovation and upholding academic integrity is essential at this time.